Improvement of physiological and productivity traits of Indian mustard (Brassica juncea) through micro-irrigation and fertigation under hot semi-arid eco-region - RATHORE, S S; SHEKHAWAT, KAPILA; KANDPAL, B K; PREMI, O P (The Indian Journal of Agricultural Sciences, 2017)
The efficient irrigation and nutrient management was done through micro-irrigation along with fertigation and the effect was evaluated on gas exchange traits, photosynthesis, growth, yield attributes and seed productivity of Indian mustard [Brassica juncea (L.) Czernj and Coss).] crop during rabi season of 2010-11 and 2011-12 respectively, under semi arid conditions. The micro-sprinkler system (MS), drip irrigation (DS) and check basin (CB) irrigation systems were experimented with variable N fertigation levels (0, 40, 80 and 120 kg/ha). The micro irrigation systems, i.e. MS, DS significantly influenced dry weight, chlorophyll concentration, photosynthetic rate, internal CO2 concentration (ICC), primary and secondary branches, main shoot length, total siliquae and 1000 seed weight. Micro-sprinkler irrigation (MS) irrigated mustard was observed on an average increase of 34 % and 23 % increase in seed yield was resulted due to drip irrigation over the two years. N-fertigation from N0 to N120 had significantly improved mustard yield attributes, seed and oil yield. Micro irrigations were also found economically viable option for irrigation in Indian mustard because of higher B: C ratio. Improvement in growth, physiological and yield attributes of mustard were ultimately enhanced seed and oil yield, irrigation water use efficiency, sustainability, yield index and production efficiency. Thus micro irrigation systems at every level of N fertigation out yielded the effect of check basin irrigation.